PENERAPAN STRATEGI PEMBELAJARAN MODEL OPEN ENDED DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS VI SD NEGERI 006 PESIKAIAN KECAMATAN CERENTI - Rita Rahim; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Based on the author's observations in grade VI SD Negeri 006 Pesikaian, it is still found that in the learning process carried out by the teacher, some students still tend to just enter the classroom carelessly. Open means open and Ended means the answer choices. The Open Enden model is a type of cooperative learning that prioritizes alternative approaches to solving problems. There are still some students who behave less well in learning such as cheating, making noise, and paying less attention to teacher explanations. There are still some students who are slow in accepting / understanding the material taught by the teacher. There are still some students who do not want to do the assignment given by the teacher.The author's problem-solving efforts carried out the following steps: 1) Observation, namely directly observing the activities in the classroom in the first cycle, and the second cycle. 2) Interviews, namely communicating directly to Islamic Education teachers and students to corroborate data from observations. Based on the results of observations and interviews with students and teachers, it was found that the root of the problem was the learning process that had not encouraged students to dare to do the tasks given by the Islamic Education teacher.The application of the open-ended model of learning strategy in increasing student learning motivation in the subject of PAI class VI SD Negeri 006 Pesikaian, Cerenti District carried out by Islamic Education teachers in the teaching and learning process is positive. The completeness graph shows that the application of the training method in Islamic Education learning can motivate student learning.